2015
DOI: 10.5152/akd.2014.5513
|View full text |Cite
|
Sign up to set email alerts
|

Serum neutrophil gelatinase-associated lipocalin levels are correlated with the complexity and the severity of atherosclerosis in acute coronary syndrome

Abstract: Objective:Neutrophil gelatinase-associated lipocalin (NGAL) is a novel inflammatory marker that is released from neutrophils. In this study, we evaluated the correlation between serum NGAL level and clinical and angiographic risk scores in patients diagnosed with non-ST elevation acute coronary syndrome (NSTE-ACS).Methods:Forty-seven random NSTE-ACS patients and 45 patients with normal coronary arteries (NCA) who underwent coronary angiography were enrolled in the study. GRACE risk score and SYNTAX and Gensini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
(29 reference statements)
1
11
0
2
Order By: Relevance
“…Some conflicting findings in the literature point that LCN-2 levels were significantly higher in acute coronary syndrome patients compared to subjects with normal coronary arteries [31] , however Giaginis et al [32] showed a contradictory result in which LCN-2 levels didn't differ between subjects with and without carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 98%
“…Some conflicting findings in the literature point that LCN-2 levels were significantly higher in acute coronary syndrome patients compared to subjects with normal coronary arteries [31] , however Giaginis et al [32] showed a contradictory result in which LCN-2 levels didn't differ between subjects with and without carotid artery stenosis.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it is thought that NGAL secreted from endothelial cells might play a role in inflammation that is associated with endothelial dysfunction and atherosclerosis [13,24]. Recent studies have demonstrated that serum NGAL concentrations are increased in CAD and might contribute to the atherosclerotic process [16,25].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, 47 patients with NSTEMI confirmed via angiography were compared to 45 control patients with stable angina (having undergone coronary angiography and determined to have normal coronary arteries), and NGAL levels were positively correlated to lesion complexity and the diffusiveness of CAD in patients with NSTEMI. It was concluded that serum NGAL levels on admission are related to the increased atherosclerotic load in patients with Non-ST elevated Acute Coronary Syndrome(NSTE-ACS) (36).…”
Section: Discussionmentioning
confidence: 99%